Effects of Democracy on Economic Growth : The Analysis of Different Democracy Indicators - Pavlas, Petr; Potužák, Pavel; Tříska, Dušan, 1946-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2022)
This thesis analyzes the effects of democracy, measured by democracy indices gathered from various datasets, on real GDP per capita growth and volatility. Volatility is calculated as the standard deviation of real GDP per capita in the period between 2005 and 2020, in line with other quantitative studies. Fundamental theoretical aspects of conceptualization and measurement of democracy are described in the thesis. Existing democracy indices are then compared in terms of these criteria. Theoretical aspects of the relationship between democracy and economic growth are introduced. The research hypotheses are approached empirically by applying regression analysis on data covering 170 countries in the period between 1990 and 2021. Firstly, models based on 2005-2020 averaged cross-sectional data are estimated. The estimated coefficients associated with democracy are statistically significant in all models. The results indicate the possibility that democracy leads to a higher real GDP per capita growth rate and a lower real GDP per capita growth volatility. Models based on panel data have not provided evidence in favor of a positive effect of democracy on real GDP per capita growth rate. In the majority of the fixed effects models, coefficients associated with democracy are statistically insignificant.
Vedoucí práce: Pavel Potužák
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: ekonomie [obor dipl. práce]; diplomové práce; master's theses